A vile passion for altering names: the contributions of Charles Thorold Wood jun. and Neville Wood to ornithology in the 1830s. Issue 2 (October 2016) - Birkhead, T. R.; Montgomerie, R.
Abstract : During the 1830s, Charles Thorold Wood jun. and his younger brother Neville Wood, published, separately, three books and a series of articles dealing with two ornithological subjects: the common and scientific names of birds, and the cataloguing of publications. Probably following William Swainson's lead, the Woods were enthusiastic about standardizing the common (English) bird names and making them logical and meaningful. They also each published an annotated bibliography of ornithological publications, notable for being among the first of such compilations, but also for the vitriol with which they criticized those – James Rennie and Hugh Strickland, in particular – whose work they did not like. In contrast, the praise they heaped on those they did approve of – William Swainson, John Latham, Robert Mudie, Prideaux John Selby, Francis Willughby and each other – was excessive. Possibly because of the tenor of their comments about other ornithologists, and the strangeness of their proposed English bird names, the Woods' work has rarely been cited, and their new names for birds were virtually ignored from the start.